MULTIDISCIPLINARY PERIODONTIA-ORTHODONTIA APPROACH IN A CASE OF MIDLINE DIASTEMA WITH LABIAL FRENECTOMY USING ELECTROSURGERY - Media sukmalia Adibah; Eka Pramudita Ramadhany; Valeo Adika Laksana; Ni Luh Desy Ayu Susilahati (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Periodontal tissue condition plays an important role as an adjunctive in the success of orthodontic therapy. One of prominent esthetic problem is midline diastema case, which was caused by high and aberrant frenulum attachment. This clinical case aims to report the frenectomy procedures with electrosurgery through multidiscipline perio- orthodontic approach to close the midline diastema. Case: : A female 19 years old patient was referred from orthodontic clinic with chief complaint there was a gap between her central insisif in upper jaw. The frenulum showed the Blanch test positive and there was no clinical attachment loss. Case Treatment: Frenectomy with electrosurgery was done to eliminate the aberrant frenulum attachment. This procedure followed with fixed orthodontic therapy to close the midline diastema and prevent any relapse. Discussions: Frenectomy can be achieved with electrosurgery which has many advantages such as coagulation, a better visualization, blood-less area, bacterimial risk reduction, an uneventful healing process, less post operative discomforts, and minimal scar tissue formation. Fixed orthodontic appliance was bonded to close the gap between central incisors. The intraoral examination showed that there was no any relaps in midline after one year follow up debonding of fixed orthodontic. Conclusion and Suggestions: a functional and esthetic outcome can be achieved through multidiscipline perio-orthodontic approach. The combination of frenectomy and orthodontic therapy showed an optimal result to close the midline diastema. Conclusion and Suggestions: a functional and esthetic outcome can be achieved through multidiscipline perio-orthodontic approach. The combination of frenectomy and orthodontic therapy showed an optimal result to close the midline diastema.